Modeling and Control Design of Quadcopter Motor - Mulyadi, Adi; Wijono, Wijono; Siswoyo, Bambang (Frontier Energy System and Power Engineering, 2020)
This paper discussed the modeling and control design of quadcoptermotor. Modeling was performed using the Laplace transformmethod. The quadcopter mathematical model was used as the loadtorque of brushless dc motor to control the stability of altitudevertical take-off motion. Motion stability was influenced by thebody frame mass, propeller speed, and wind disturbance duringhovering. Hence, the quadcopter motion experienced oscillation toreach a steady state. The tuning of Ziegler-Nichols PID and fuzzygain scheduling PID were suggested to overcome the stability ofaltitude vertical take-off motion. The simulation results showed thatfuzzy gain scheduling PID reduced the overshoot 0.1% smaller thanthe Ziegler-Nichols tuning.